Key elements of the Polish stand on the European Union Eastern policy (Economic and Political Thought, 2015)
As early as in the period before the enlargement of the European Union in2004, Poland – as a candidate state at the time – took part in the debate beforethe European Neighbourhood Policy (formally introduced just a few days afterthe 2004 enlargement) was conceived. During the debate, the key issue wasthe idea of further enlargement of the EU after adequate requirements aremet. One of the most important elements of the Polish programme within theEU Eastern policy in the period 2006–2014 was energy and activities withinthe Eastern Partnership. After Sweden supported the Eastern Partnershipat its initial stage, Poland gained a lot of positive experience. A supposedpermanent element of the Polish strategy within the EU Eastern policy wasalso its consent for the strengthening of common EU institutions, especiallyin the internal policy, which might have been interpreted as promoting theprinciple of “more enlargement for deepening” the co-operation withinthe EU. It can be perceived as an element of transaction with the memberstates that were against or sceptical about enlargement and/or an attempt tostrengthen Polish stand within the EU Eastern policy with the use of commoninstitutions. A specific canon of the Polish stand within the EU Eastern policyrelated to the Polish political thought tradition has developed over the last15 years. From the point of view of the catalogue of Polish targets, one cannotice a tendency in the EU to accept some Polish arguments as commonones – it is seen when the development of the idea and implementation of theENP is compared with what resulted from the Eastern Partnership.